ТҮРКИЙ ХАЛЫҚЛАРДА МИЙЎЕЛИ АҒАШ ҲӘМ ХАЛЫҚ САЛТ-ДӘСТҮРЛЕРИ ҲАҚҚЫНДА - Сапарниязов, Р. (FAN va JAMIYAT, 2021)
This article studies the fruit tree and the meaning of the tree in human’s life, holiness of tree, determination of comparative studying about the concept of tree with the customs related to the folklore of Turkic people.